Electrical pumping and tuning of exciton-polaritons in carbon nanotube microcavities - Graf, Arko; Held, Martin; Zakharko, Yuriy; Zaumseil, Jana (Nature materials, 2017)
Exciton-polaritons are hybrid light-matter particles that form upon strong coupling of an excitonic transition to a cavity mode. As bosons, polaritons can form condensates with coherent laser-like emission. For organic materials, optically pumped condensation was achieved at room temperature but electrically pumped condensation remains elusive due to insufficient polariton densities. Here we combine the outstanding optical and electronic properties of purified, solution-processed semiconducting (6,5) single-walled carbon nanotubes (SWCNTs) in a microcavity-integrated light-emitting field-effect transistor to realize efficient electrical pumping of exciton-polaritons at room temperature with high current densities (>10 kA cm−2) and tunability in the near-infrared (1,060 nm to 1,530 nm). We demonstrate thermalization of SWCNT polaritons, exciton-polariton pumping rates ~104 times higher than in current organic polariton devices, direct control over the coupling strength (Rabi splitting) via the applied gate voltage, and a tenfold enhancement of polaritonic over excitonic emission. This powerful material-device combination paves the way to carbon-based polariton emitters and possibly lasers.